2022
DOI: 10.1111/jeb.14007
|View full text |Cite
|
Sign up to set email alerts
|

Divergent selection on behavioural and chemical traits between reproductively isolated populations of Drosophila melanogaster

Abstract: Speciation is driven by traits that can act to prevent mating between nascent lineages, including male courtship and female preference for male traits. Mating barriers involving these traits evolve quickly because there is strong selection on males and females to maximize reproductive success, and the tight co‐evolution of mating interactions can lead to rapid diversification of sexual behaviour. Populations of Drosophila melanogaster show strong asymmetrical reproductive isolation that is correlated with geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 144 publications
(227 reference statements)
1
12
0
Order By: Relevance
“…Both shep and Nrg regulate neurological development, specifically neural remodeling during metamorphosis, contributing heavily to the formation of higher learning centers, specifically those responsible for processing olfactory signals (Carhan et al, 2005; Chen et al, 2014). This complements a gene ontology analysis of outliers for female mate preference by Coughlan et al (2021) that found significant outliers involved in sensory perception, including three olfactory receptors, as well as genes important for learning and memory, cognition, and neurological development.Both of these analyses are consistent with previous work in these populations of D. melanogaster has suggested a large role for olfaction in female mate preference (Grillet et al, 2012; Moran, 2006; Jin et al, 2022). Given these complementary observations it will be important to understand how differences in Nrg and shep alleles potentially correlation with structural and/or functional changes in the neural networks of females that show high or low mate discrimination preference and whether this is correlelated with the olfactory cues used in mate preference.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Both shep and Nrg regulate neurological development, specifically neural remodeling during metamorphosis, contributing heavily to the formation of higher learning centers, specifically those responsible for processing olfactory signals (Carhan et al, 2005; Chen et al, 2014). This complements a gene ontology analysis of outliers for female mate preference by Coughlan et al (2021) that found significant outliers involved in sensory perception, including three olfactory receptors, as well as genes important for learning and memory, cognition, and neurological development.Both of these analyses are consistent with previous work in these populations of D. melanogaster has suggested a large role for olfaction in female mate preference (Grillet et al, 2012; Moran, 2006; Jin et al, 2022). Given these complementary observations it will be important to understand how differences in Nrg and shep alleles potentially correlation with structural and/or functional changes in the neural networks of females that show high or low mate discrimination preference and whether this is correlelated with the olfactory cues used in mate preference.…”
Section: Discussionsupporting
confidence: 91%
“…The two male strains used in the experiment are phenotypically indistinguishable, so to be able to tell them apart we placed them on food containing blue food coloring 48 hours prior to the bheavioral assay. This is a non-invasive, robust identification method that does not affect male courtship behavior or female preference (Wu et al, 1995; Hollocher et al, 1997; Coughlan et al, 2021; Serrato-Capuchina et al, 2021; Jin et al, 2022). All behavioral assays were performed in a room held at a constant 20C degrees Celsius and 50% humidity within two hours of the incubator lights turning on to maximize the number of copulations we could observe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations